If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4k + -9k = 10j Combine like terms: 4k + -9k = -5k -5k = 10j Solving -5k = 10j Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Divide each side by '-5'. k = -2j Simplifying k = -2j
| 12x(3x-3)-6x(7x-9)= | | 4(2x+3)=7x+4 | | B(b-7)= | | x^2+18x+19=8x-5 | | 4(10d-4)=64 | | x^2+4x+9=6 | | 10(d-4)=60 | | 3x+2x=4x-8 | | 5(3x+3)=30 | | 2(2m-1)=18 | | 5(m-1)=30 | | 3(5a+2)=36 | | 4(2x)-(x+5)= | | 11u-88=3u | | 3(4x-1)=21 | | 0.5(9x+18)=-1.5(5x)-2(3x+4.5) | | 3x^3+26x^2+35x=0 | | 7w=5w+16 | | 3(3y+5)=5y+25 | | graphy=7+10x | | (x-6)(3x+4)=0 | | y=7+10x | | (1/2)(2x-10)=4 | | x^3-3x^2+9x-54=0 | | x^2-4=6 | | 8(y-5)=6-18 | | .20x+.25+9=.21 | | 4-15y=4 | | -14=(2/5)(9-2b) | | -32=(8/7)(3w-1) | | .80x+.25(60)=.70(x+60) | | c=0.90y+1.65 |